2015
DOI: 10.1007/s11356-015-5111-5
|View full text |Cite
|
Sign up to set email alerts
|

Compost addition reduces porosity and chlordecone transfer in soil microstructure

Abstract: Chlordecone, an organochlorine insecticide, pollutes soils and contaminates crops and water resources and is biomagnified by food chains. As chlordecone is partly trapped in the soil, one possible alternative to decontamination may be to increase its containment in the soil, thereby reducing its diffusion into the environment. Containing the pesticide in the soil could be achieved by adding compost because the pollutant has an affinity for organic matter. We hypothesized that adding compost would also change s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…It has to be noted that different research programs are still in place to investigate CLD sequestration by the use of organic amendments like compost (decayed organic material from plants) (Woignier et al 2016). Regarding the use of compost, one major problem is related to its durability.…”
Section: Comparison Of Strategies Applied To Limit Cld Transfer To Fl...mentioning
confidence: 99%
“…It has to be noted that different research programs are still in place to investigate CLD sequestration by the use of organic amendments like compost (decayed organic material from plants) (Woignier et al 2016). Regarding the use of compost, one major problem is related to its durability.…”
Section: Comparison Of Strategies Applied To Limit Cld Transfer To Fl...mentioning
confidence: 99%
“…As a result, the only agricultural practices that could have increased CLD leaching are the one that modified environmental characteristics that affect pesticide transfers (Mottes et al 2014). Here, modifications of the soil organic matter content, allophane clay content, or both potentially decreased CLD retention by soil (Woignier et al 2016;Woignier et al 2012a;Woignier et al 2012b;Woignier et al 2013). It has been shown that the peculiar hierarchical (fractal) microstructure of allophane clay traps CLD (Woignier et al 2012a;Woignier et al 2013).…”
Section: Effects Of Cropping Practicesmentioning
confidence: 99%
“…Soil amendments have been shown to influence soil pesticide processes like leaching and degradation (Cox et al 2001;Thevenot et al 2009). We have recently proposed an alternative to the complete decontamination (Clostre et al 2014b;Woignier et al 2013Woignier et al , 2016: the sequestration by the addition of compost. We showed that the addition of 5 wt% of compost strongly decreases the soil-to-water and to vegetables transfers of CLD (pot experiments).…”
Section: Alternative Techniques To Decontaminationmentioning
confidence: 99%